Manipulative Basic Motion Learning Model for The Elementary School Level - Sukmawati, Noviria; Oktariyana, Oktariyana; Zulkarnain, Ferdi (Department of Physical Education, Sport, Health and Recreation, 2020)
The purpose of this study was to produce a manipulative basic motion learning model product at the elementary school level. This study uses a research and development method that adopts the theory of Borg and Gall which has 10 development steps. However, the research only reached the 7th step, namely Operational product revision. This research uses a descriptive qualitative approach. The results of this study are in the form of a manipulative basic motion learning model product at the elementary school level which has been proven to be suitable for use by elementary school level students because it has gone through the trial stages, namely the validation of experts and field trials both small-scale trials and large-scale trials. So it can be concluded that, the final product in this study is in the form of a manipulative basic motion learning model textbook that is feasible for use at school level students which are expected to be used as a reference in the physical education learning process at the elementary school level.